(untitled) - Wysocki, Robert K. (New York, 1990)
Designed as a supplement to the text Information Systems: Management Principles in Action, this collection of real-world vignettes provides students with challenging applications based on the actual problems faced by information systems managers. The vignettes illustrate complex management problems at the corporate, functional, and end-user levels, most of which center around the evaluation of alternative decisions the information systems manager might make and the consequences of those decisions. Topics include information technology as a competitive weapon, strategic information systems planning, the organizational placement of the information systems department, corporate issues and opportunities, specific duties of the information systems department, organizing the information systems department, and much more.
Keywords: Management information systems,Quản lý hệ thống thông tin; Case studies,Nghiên cứu tính huống